THE INDEGENEOUS PEOPLES AND DEVELOPMENT OF ARCHITECTURE AND INTERIOR BALI TRADITIONAL HOUSE IN MUNCAN CUSTOMARY VILLAGE, KARANGASEM, BALI - Nutrisia Dewi, Ni Made Emmi; Pranajaya, I Kadek; Yuni Utami, Ni Kadek (E-Journal of Cultural Studies, 2022)
The existence of indigenous peoples is one of the important things in supporting the sustainability of traditional values, especially those related to the design of residential buildings. The customary village of Muncan Village, Karangasem is one of the traditional villages in Bali where the existence of indigenous peoples still exists. This can be seen from the lives of these indigenous peoples in carrying out their daily lives still following the customs and rules contained in the region. Seeing the high existence of indigenous peoples in the village, it is necessary to examine the relationship of the existence of indigenous peoples to the development of architecture and interiors in these traditional Balinese houses. The purpose of this study was to determine the role of indigenous peoples in preserving traditional Balinese houses. This study uses a method with a qualitative approach and a cultural studies perspective. The results of this study indicate that the existence of indigenous peoples in the village of Muncan affects the architectural and interior development of their homes. This can be seen from the mindset of the community as well as various activities that contain elements of religion, tradition and belief that are applied to the architectural design of their residences. Broadly speaking, the architectural design of the residence still applies the concept of traditional Balinese architecture but has developed only in the form of materials and forms following developments according to the latest science and technology. Keywords: Existence, Society, Custom, Architecture, Interiors.